The Analysis of The Influence of Digital Marketing and Product Diversity on The Success of E-Commerce Business - Lazuardi, Dedy; Rinaldi, Muammar; Shinta, Shinta (Outline Publisher, 2023)
This research examines the factors influencing the success of e-commerce, focusing on Digital Marketing and Product Diversity as independent variables. The study takes place at RADATIME, an e-commerce store in Medan that specializes in selling watches. Digital Marketing and Product Diversity were chosen due to their significant impact on Business Success, which is measured through indicators such as Competitiveness, Business Competence, and Business Ethics. A quantitative method was employed, involving the distribution of questionnaires to 96 RADATIME customers randomly selected from a total of 2,371 customers in 2022 (with a 10% margin of error). The analysis reveals that Business Success = 2.250 + 0.506 Digital Marketing + 0.587 Product Diversity + e, indicating a positive and significant influence from both variables. The t-test results for Digital Marketing (t-value = 6.433, significance level = 0.000) and Product Diversity (t-value = 5.003, significance level = 0.000) support this finding. Additionally, the F-test indicates a significant simultaneous effect of both variables (F-value = 126.747, significance level = 0.000). The coefficient of determination (R2 = 0.732 or 73.2%) demonstrates that 73.2% of Business Success can be explained by Digital Marketing and Product Diversity, while the remaining 26.8% is attributed to unexplored variables. Future research should consider incorporating or replacing independent variables with greater influence.